Microencapsulation in the Food Industry: Current Advances and Trends (CIENCIA Y TECNOLOGÍA AGROPECUARIA, 2024)
Microencapsulation in the food industry has emerged as a promising technique to improve the quality, safety and functionality of food products, responding to the growing demand for functional and nutritionally improved foods. The problem lies in the need to protect active ingredients sensitive to environmental factors during food processing and storage. The present review research aims to analyze the impact of microencapsulation on the stability of ingredients and its relevance in the food industry. The research was based on an exhaustive bibliographic review of sources specialized in food microencapsulation at a national and international level. Specific search criteria in scientific databases were used to select relevant documents. Microencapsulation protects sensitive ingredients from external factors such as light, oxygen and humidity allowing the creation of functional foods with improved health properties and contributes to the stability and bioavailability of active ingredients in foods. Microencapsulation in the food industry is a key technique to improve the quality and functionality of products, offering benefits such as protection of sensitive ingredients and creation of functional foods. Its application can be essential to meet the demands of modern consumers and promote innovation in the food industry.
Keywords: innovation; active ingredients; stability; functional foods